Development of residential flood depth-damage curve for Kuantan, Pahang - Nur Izyan Hani, Mohd Razaki (2018)
In recent years floods occur frequently and cause severe impacts to the flooded areas. It is consequently an important issue of many countries to prevent and mitigate flood damage. The aim of this study is to assess the direct tangible flood damage experienced by the victims of 2013 Kuantan flood and to identify the factors that influence the level of flood damage. A residential flood depth-damage curve is developed based on the damage data collected during interview survey. The percentage of damage is calculated by dividing the estimated structural/content damage with the actual damage value. According to the types of construction materials, the average structural damage is RM2642, RM2250 and RM2120 for brick, wood and brick and wood house respectively. The content damage for all types of materials is higher which is between RM 4104 to RM 4556 per property. Most of the houses are one storey terrace house with average value of damage is RM 2250 per property. From the SPSS analysis, the rate of damage was influenced by house‟s price, construction materials and household income. With R2 of 0.98 and 0.82 for content and structural damage respectively, the flood depth-damage curves obtained in this study is good enough and can be used for future studies on flood risk assessment of the study area.